Serum Cotinine Levels, Smoking, and Periodontal Attachment Loss - Gonzalez, Y.M.; De Nardin, A.; Grossi, S.G.; Machtei, E.E.; Genco, R.J.; De Nardin, E. (Journal of dental research, 1996)
Cigarette smoking and tobacco use have been the subjects of numerous studies for many years. Smoking has also been associated with periodontal disease. However, no relationship between a reliable biochemical marker and increased severity of the periodontal condition has yet been described. It was thus the aim of this study to apply the measurement of cotinine, the major metabolite of nicotine, as a quantitative method to assess levels of smoking, and to correlate serum levels of cotinine with severity of periodontal disease. The degree of association between smoking and periodontal attachment loss was investigated in a study including 79 patients 25 to 64 years old suffering from periodontitis. Patients were examined and the following parameters recorded: Gingival Assessment (GA), Probing Pocket Depth (PPD), Clinical Attachment Level (CAL), and Bone Crest Height (BCH). In addition, self-reported histories of tobacco use as well as blood samples for quantitative analysis of serum levels of cotinine were taken. The serum samples were analyzed for cotinine content by means of a competitive-inhibition ELISA technique. The differences in mean cotinine levels were statistically significant (p = 0.0001) between smokers and non-smokers, showing no overlap between the groups. Severity of periodontal attachment loss was positively correlated with serum levels of cotinine for both measures of periodontal disease (CAL p = 0.005; BCH p = 0.008). Results from the present study indicate that serum cotinine levels used as a biochemical marker of smoking status are correlated with severity of periodontal attachment loss.